PERBANDINGAN RISIKO LIKUIDITAS DAN TINGKAT PROFITABILITAS PENERAPAN ASSET LIABILITY MANAGEMENT PADA BANK YANG TERDAFTAR DI BURSA EFEK INDONESIA - Karnawi Kamar; Pandu Adi Cakranegara; Karina Dewi Sartika; Rahman Yakub (Economos : Jurnal Ekonomi dan Bisnis, 2022)
The emergence of Covid 19 in the Industrial Era 4.0 where countries in the world are competing to innovate in various fields, both health, education, and the economy to be able to follow the era towards the era of Society 5.0. The purpose of this study was to analyze differences in liquidity risk and profitability level in the application of asset management between state banks and national private banks. The analytical method used is descriptive comparative analysis by providing an overview of the liquidity ratios and profitability levels in the application of asset management at State Banks and National Private Banks listed on the Indonesia Stock Exchange using the formula Cash Ratio and Return on Assets. The results of the study indicate that (1) there is no difference in liquidity risk in the application of asset liability management between state banks and national private banks. The liquidity of the two banks is equally well above the standard set by Bank Indonesia, but there is no insignificant difference in terms of the amount of liquidity. (2) there is no difference in the level of profitability in the application of asset liability management between state banks and national private banks. The profitability of the two banks is above the standard set by Bank Indonesia, but in terms of profitability, there is a slight difference which is not significant.